A descending dopamine pathway conserved from basal vertebrates to mammals - Ryczko, Dimitri (Proc Natl Acad Sci U S A, 2016)
Dopamine neurons are classically known to modulate locomotion indirectly through ascending projections to the basal ganglia that project down to brainstem locomotor networks. Their loss in Parkinson’s disease is devastating. In lampreys, we recently showed that brainstem networks also receive direct descending dopaminergic inputs that potentiate locomotor output. Here, we provide evidence that this descending dopaminergic pathway is conserved to higher vertebrates, including mammals. In salamanders, dopamine neurons projecting to the striatum or brainstem locomotor networks were partly intermingled. Stimulation of the dopaminergic region evoked dopamine release in brainstem locomotor networks and concurrent reticulospinal activity. In rats, some dopamine neurons projecting to the striatum also innervated the pedunculopontine nucleus, a known locomotor center, and stimulation of the dopaminergic region evoked pedunculopontine dopamine release in vivo. Finally, we found dopaminergic fibers in the human pedunculopontine nucleus. The conservation of a descending dopaminergic pathway across vertebrates warrants re-evaluating dopamine’s role in locomotion.